Cases of Abnormality of Horse Hooves (Equus caballus) In Santosa Stable Kendal-Central Java - Henny Endah Anggraeni; Tahfida Imania Nisa (Journal of Applied Veterinary Science And Technology, 2023)
Background: Horse hoof abnormalities are one of the most frequent disorders in horses and the leading causes affecting the productivity of horses. Purpose: Explanation of the percentage of abnormalities of Andalusian, Warmblood, and Generasi horses in Santosa Stable. Method: Qualitative methods in this study used a qualitative research approach case study. Results: Hoof abnormalities occurred in 6 horses (1 stallion and 1 Andalusian mare, 1 Warmblood mare, 2 G4 stallions, and 1 G3 horse). Cases of hoof crack (31.25%) and hoof rings (12.5%). Conclusion: Hoof crack is the most common abnormality found in horses in Santosa Stable